Pengaruh Kunjungan Wisatawan pada Masa Covid-19 terhadap Penyerapan Tenaga Kerja di Provinsi Bali Pada Tahun 2019-2021 - Ni Wayan Anggreni (Jurnal Kajian dan Terapan Pariwisata, 2022)
This research was motivated by the results of previous studies which stated that in 1998-2015 tourist visits did not directly affect employment in the Province of Bali. However, it is different from the current situation, when Covid-19 is declared to have an impact on the economy, one of which is in Bali from 2019 to 2021 due to the decline in revenue from tourism which is accompanied by a decline in the performance of the tourism sector that has occurred in Bali, of course this will not be allowed to continue for long. Various efforts have been made to revive tourism, one of which is by adapting to a new order of life. This study aims to determine the effect of tourist visits during the Covid-19 period on working residents aged 15 years and over in the Province of Bali in 2019-2021. The type of data collected in this study is quantitative and qualitative data. The Source of data in this research is secondary data. Documentation is a method of collecting data in this study. Data analysis methods consist of the classical assumption test, normality test, multicollinearity test, heteroscedasticity test, t-test (partial test), and test of the coefficient of determination (R2). The results of this study indicate that tourist visits (X) during the Covid-19 Period had no effect on working residents aged 15 years and over in the Province of Bali in 2019-2021. The impact of tourist visits during the Covid-19 period on working residents aged 15 years and over in the Province of Bali in 2019-2021 is 75.9%.